Recapture voice replay detection based on phase spectrum - Can LI; Rangding WANG; Diqun YAN; Yanan CHEN (Dianxin kexue)
Due to a high similarity between the recaptured voice recorded by high-fidelity ripping equipment and the original voice,the automatic speaker verification（ASV）system used to be attacked illegally by the recaptured voice.In order to improve the ability of resisting the attack,a recaptured voice detection method was proposed based on the difference of phase spectrum between original and recaptured voices for the ASV system.In addition,the effects of different recording and replay devices,the FFT were discussed.Experimental results show that the proposed method can accurately recognize the recording voice,of which detection rate is 99.04%。Meanwhile,the equal error rate (EER) of the ASV system has dropped about 22% with this method being integrated,which indicates that the system’s ability of resisting playback attack is enhanced.